2015
DOI: 10.1007/s00412-015-0565-2
|View full text |Cite
|
Sign up to set email alerts
|

The 14/15 association as a paradigmatic example of tracing karyotype evolution in New World monkeys

Abstract: Fluorescence in situ hybridization (FISH), especially chromosome painting, has been extensively exploited in the phylogenetic reconstruction of primate evolution. Although chromosome painting is a key method to map translocations, it is not effective in detecting chromosome inversions, which may be up to four times more frequent than other chromosomal rearrangements. BAC-FISH instead can economically delineate marker order and reveal intrachromosomal rearrangements. However, up to now, BAC-FISH was rarely used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…This evidence is supported by what is shown in the other species here analyzed, where the 14/15 syntenic association is present and human probe 14 is split into two fragments. The different size of human synteny 14 (in association with synteny 15) in the species analyzed indicates that the fissions presumably occurred with different breakpoints and are consistent with the high level of rearrangements previously shown in other primate taxa [ 49 , 50 ]. Human probe 15 can also be found in a single block or split into two blocks in the analyzed taxa ( Table 1 ).…”
Section: Discussionsupporting
confidence: 84%
“…This evidence is supported by what is shown in the other species here analyzed, where the 14/15 syntenic association is present and human probe 14 is split into two fragments. The different size of human synteny 14 (in association with synteny 15) in the species analyzed indicates that the fissions presumably occurred with different breakpoints and are consistent with the high level of rearrangements previously shown in other primate taxa [ 49 , 50 ]. Human probe 15 can also be found in a single block or split into two blocks in the analyzed taxa ( Table 1 ).…”
Section: Discussionsupporting
confidence: 84%
“…Unfortunately, different approaches (bioinformatics, cytogenetics) often provide conflicting results about the number and types of rearrangements. In some taxa, it was shown that intrachromosomal rearrangements are more frequent than interchromosomal rearrangements 31 , 35 , 36 . Notably, the contribution of intrachromosomal rearrangements was more significant in rapidly evolving groups.…”
Section: Discussionmentioning
confidence: 99%
“…Materials from another species ( Aotus lemurinus ) were also used in the present study for confirmation of the results obtained from A. azarae . The cell line of A. lemurinus was obtained from the Foundation Biomedical Primate Research Center, the Netherlands as previously reported ( Capozzi et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%